Ενίσχυση κτιρίων από οπλισμένο σκυρόδεμα - Κυριζή, Κυριάκος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The present thesis describes a structural design for an existing building made of reinforced concrete, which was built in 1986 and in which two new floors are intended to be built. The existing building is a typical single-storey house which was designed based on older anti-seismic regulations, however without significant damage to it. The thesis is divided into two main sections; the first one concerns the theoretical background whereas the second section analyses the procedure adopted in the study, for the creation of the two new floors as well as for the reinforcement of the existing structure. In the theoretical background section, the ‘pathology’ of the construction is initially explained; meaning the damages developed in the load-bearing structure of a construction of reinforced concrete and their causes. The theory of Eurocode 8 Part 3 is then analysed, in order to explain the performativity levels chosen by the developer, and to get the necessary information to be able to assess and evaluate the existing structure (required data, reliability levels and levels of knowledge). Furthermore, based on Eurocode 8 Part 1, the four methods of analysis of a seismic response of a building are examined – the Lateral Force Method of Analysis, the Modal Response Spectrum Analysis, the Non-Linear Static (pushover) Analysis and the Non-Linear Time History (dynamic) Analysis. Lastly, in the theoretical background section, the various methods of control and testing of the building materials of an existing structure are explained, along with the different methods of support, depending on the existing problems of each part of the load-bearing structure. The second and final part initially explains the procedure followed by the 3DR.STRAD 2014 software for the analysis of the building based on the Eurocodes and to conclude, the results of the analysis of the present software are presented and further discussed.
Keywords: Reinforced concrete; Construction pathology; Lateral force method of analysis; Modal response spectrum analysis; Non-linear static (pushover) analysis; Non-Linear time history (dynamic) analysis; Οπλισμένο σκυρόδεμα; Παθολογία κατασκευών; Μέθοδος ανάλυσης οριζόντιας φόρτισης; Ιδιομορφική ανάλυση φάσματος απόκρισης; Μη γραμμική στατική ανάλυση; Μη γραμμική ανάλυση χρονοϊστορίας